Glycerol Monolaurate to Ameliorate Efficacy of Inactivated Pseudorabies Vaccine - Ren, Qinghai; Wang, Xiaobo; Gao, Qingqing; Wang, Gaiqin; Chen, Xiaochen; Liu, Chunxue; Gao, Song; Li, Yubao (Frontiers in Veterinary Science, 2022)
The present study is aimed to evaluate the effect of glycerol monolaurate (GML) on the growth performance and immune enhancement of pseudorabies virus (PRV)-inactivated vaccine in the early-weaned piglets. One hundred and twenty-five 28-day-old weaned piglets were randomly assigned to a control group (CON, no vaccine and no challenge), challenge control group (C-CON), inactivated PRV vaccine group (IPV), IPV + 500 mg/kg GML group (L-GML), and IPV + 1,000 mg/kg GML group (H-GML) during the entire 28-day experimental period. All the data analyses were performed by one-way analysis of variance (ANOVA) and multiple comparisons. Our results showed that the final weight, average daily gain (ADG), and average daily feed intake (ADFI) of H-GML were the highest in each group, and F/G of H-GML was increased but there was no significant difference with CON (p > 0.05). Levels of PRV glycoprotein B (gB) antibody and immunoglobulin in serum of L-GML and H-GML were higher than those of IPV, but only gB antibody levels and immunoglobulin G (IgG) in H-GML were significantly increased (p < 0.05). Compared with IPV, the contents of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β) in serum of L-GML (TNF-α and IL-1β: p > 0.05, IL-6: p < 0.05, respectively) and H-GML (p < 0.01, both) were all decreased, and the content of interleukin-10 (IL-10) in H-GML was increased (p > 0.05). Furthermore, reverse transcription-polymerase chain reaction (RT-PCR) experiments proved that L-GML and H-GML were both superior to IPV in inhibiting the expression of TNF-α (p < 0.01), IL-6 (p > 0.05), and IL-1β (p < 0.01) mRNAs and promoting the expression of IL-10 mRNA (L-GML: p > 0.05, H-GML: p < 0.05, respectively) in the superficial inguinal lymph nodes. Histopathological examination found mild congestion in the lung and inguinal lymph nodes of IPV, while the tissues (brain, lung, and inguinal lymph nodes) of L-GML and H-GML were the same as CON with no obvious lesions. The above results indicate that GML may improve the growth performance of weaned piglets and enhance the immunity of PRV-inactivated vaccine by increasing the levels of PRV gB antibody and immunoglobulin and regulating cytokine levels.